Hydroxychloroquine, azithromycin and methylprednisolone and in hospital survival in severe COVID-19 pneumonia - Go, Ronaldo C.; Nyirenda, Themba (Frontiers in Pharmacology, 2022)
Introduction: Severe COVID-19 pneumonia has two phases that are not mutually exclusive. Repurposed drugs target only one phase and the association of combination therapy to survival is unknown. Objective: To determine the association of hydroxychloroquine, azithromycin, and methylprednisolone versus methylprednisolone only to in hospital survival. Methods: This is a secondary analysis of a retrospective cohort of patients admitted for severe covid-19 in 13 hospitals in New Jersey, United States from March–June 2020. Propensity score match with 11 variables was constructed between those who received no methylprednisolone and methylprednisolone. Multivariate Cox regression was used for risk of in hospital mortality. Measurements and main results: There were 759 patients, 380 in no methylprednisolone and 379 with methylprednisolone. Multivariate Cox regression shows that methylprednisolone, hydroxychloroquine, and azithromycin had prolonged survival compared to methylprednisolone alone [HR 0.45 (95% CI 0.22,0.91 p < 0.03)]. In patients who received hydroxychloroquine and azithromycin, those who also received high dose methylprednisolone were associated with worse survival compared to those who received low dose methylprednisolone (HR = 1.642; 95% CI 1.053 to 2.562; p = 0.0287). Nursing home residents [HR 2.77 (95% CI 1.67, 4.59 p < 0.0001)], coronary artery disease [HR 2.93 (95% CI 1.31, 3.15 p = 0.001), and invasive mechanical ventilation [HR 3.02 (95% CI 1.71,5.34 p = 0.0001)] were independently associated with worse survival. Conclusion: Combination therapy was associated with improved survival compared to monotherapy. However, nursing home residents, coronary artery disease, and mechanical ventilation were independently associated with mortality. Larger randomized controlled studies are needed to confirm conclusions.